An efficient synthesis, structural analysis, and computational studies of benzothiazole derivatives activated by formic acid under solvent-free conditions - Karzan Aziz Abdalkarim; Sewara Jalal Mohammed; Aso Hameed Hasan; Khalid M. Omer; Francisxavier Paularokiadoss; Rebaz Fayaq Hamarouf; Kosar Hikmat Hama Aziz; Hanar Qadir Hassan; Thayalaraj Christopher Jeyakumar (Chemical Physics Impact, 2024)
In the present work, formic acid was used as a low-cost and eco-friendly catalyst to synthesize 2-(2-hydroxyphenyl)benzothiazole (HB) through a cycloaddition process in a solvent-free reaction medium. Imine molecule was synthesized with the help of acetic acid (B). The ring closure and formation of the thiazole moiety give acetic acid distinctiveness as a catalyst. The cyclization of fused HB failed without an acid catalyst. The chemical structures were characterized using microanalysis techniques such as IR, 1H-NMR, and 13C-NMR. The obtained FT-IR spectra were compared to theoretical data using the B3LYP/6-31G* level of theory. The electronic characteristics of molecules can be predicted utilizing wave function-dependent features, such as Average localized ionization energy (ALIE), Localized orbital locator (LOL), Electron localized function (ELF), Reduced density gradient (RDG), and Noncovalent interactions NCI studies, which have provided a wealth of knowledge. The molecular docking study was investigated to explore binding energy and interaction type. Docking analysis displayed binding energies (kcal/mol) of HB with values of -8.29, -6.80, -6.68, -7.43, and -6.69 of acetylcholinesterase (AChE) and butylcholinesterase (BuChE)), SARS-CoV-2 main protease (Mpro), human immunodeficiency virus reverse transcription (HIV RT)) and cytochrome (P450), respectively, which was the most active compound against all receptors. The dramatic improvement of the proposed approach over the existing methods can be used to derive an efficient and successful route for the synthesis of HB. This process provides a fresh and high-yield method for the synthesis of benzimidazoles.